A circular economy approach to drinking water treatment residue management in a catchment impacted by historic metal mines - Nunn, Benjamin; Lord, Richard; Davidson, Christine M. (Journal of environmental management, 2023)
Drinking water treatment residues (DWTR) from mining areas which remove and contain potentially toxic elements (PTE) could still potentially be used as a soil amendment to restore contaminated sites in the same catchment, thus eliminating waste and reducing the chemical and physical mobility of the pollutants. To assess this restorative and regenerative approach to DWTR management, field and pot trials were established with soils from a historic Pb–Zn mine site in the North East of England, amended with either local DWTR or the nearest available municipal green waste compost (GWC). Soils from the mine site were found to have very low levels of nutrients and very high levels of PTE (Pb and Zn > 13, 000 mg/kg). The perennial grass species Phalaris arundinacea, known for many ecosystem service benefits including soil stabilization, was used throughout this study. The application of the BCR sequential extraction to soils amended with the DWTR in the pot trials found a significant decrease in the bioavailability of Pb and Cu (p < 0.05) after plant growth when compared with an unamended control. The field trial involved 648 pre-grown grass plants planted-out into mine soils amended with either DWTR, GWC or a mixture (MIX) of the two, all at rates of 25–30% w/w. Both amendments and the MIX had significant positive effects on biomass production compared to the unamended control in the following order GWC > MIX > DWTR (p < 0.05). Results of the elemental analysis of biomass from the field trial were generally ambiguous and did not reflect the decreased bioavailability noted in the pot trials using the BCR procedure. Pot trials, however, showed increases in plant growth and decreases in concentrations of Cr, Cu, Pb and Zn in above ground biomass following the application of both amendments. Further work should involve the testing of a mixture of DWTR and other soil amendments to enhance plant growth. The success of these trials should provide confidence for those working in drinking water treatment and catchment management to reuse the waste residues in a circular economy and a sustainable way that could improve water quality over time. [Display omitted] •Drinking water treatment residues in mining areas can remediate contaminant sources•Pot and field trial results support use of these residues as a soil amendment•Circular economy approach to eliminate waste and restore impacted catchment